Micmac Farms: From Community Garden to Four-Season Farm and Retail Outlet - Caulfield, Jane (Maine Policy Review, 2011)
This short case study describes how Maine’s Micmac tribe is developing “Micmac Farms” from a community garden to a four-season agricultural business.